Cloud Computing Technologies and the Economic Impact of Digitalization - Ignat, Gabriela; Sargu, Lilia; Prigoreanu, Ioan (EuroEconomica, 2022)
Nowadays, the use of the Internet and new technologies, for business and people, is part of everyday life. Thanks to the Internet, any information is available anywhere in the world at any time, and this was not available a few years ago. The term Cloud Computing describes a variety of concepts that involve a large number of computers connected through a network in real time, this being possible with the help of the Internet. Cloud computing is the most popular and widely used technology today.Big data, storage capacity and inadequate analysis are challenging many organizations today and require perfect data management techniques and analytical models to implement an integrated business intelligence solution.